The Effectiveness of Communication Training and the Application of Structured Communication Methods on Handover Quality, Patient Safety, and Nurse Performance in Hospitals: A Systematic Review - Ni Luh Putu Seriwidhayanti; Elsye Maria Rossa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Effective communication is a critical component of the nursing handover process and directly contributes to patient safety. This systematic review aims to identify, evaluate, and synthesize scientific evidence regarding the effectiveness of communication training and the implementation of structured communication methods on handover quality, patient safety, and nurse performance in hospitals.A literature search was conducted in PubMed, Scopus, and CINAHL databases for studies published between 2010 and 2025. Studies that met the inclusion criteria included randomized controlled trials (RCTs) and quasi-experimental studies that provided interventions such as communication training or the implementation of structured communication methods for hospital nurses. Study selection followed the PRISMA 2020 guidelines, while methodological quality assessment was conducted using the Joanna Briggs Institute (JBI) instrument. From 678 articles, we found total of 10 eligible studies were synthesized narratively due to the heterogeneity of interventions and outcomes. The synthesis showed that communication training and structured communication methods consistently improved the completeness, clarity, and accuracy of handovers; strengthened team coordination; and reduced the risk of communication errors that impact patient safety. RCTs demonstrated significant improvements in nurses' communication competency and clinical performance, while quasi-experimental studies confirmed the practical effectiveness of SBAR/ISBAR implementation in various hospital units. Contextual factors such as workload, organizational culture, and leadership support also influenced implementation success. Communication training and structured communication methods have proven effective in improving handover quality, patient safety, and nurse performance.